Relationship Between Leadership Style and Conflicts in Family Businesses - Priscila Sardi Cerutti; Carlos Costa; Jandir Pauli; Luciana Cristina Laval (BBR: Brazilian Business Review)
The themes of managerial style and interpersonal conflicts in a business context have been discussed, but their relationship, especially in family organizations, has seen little or no attention. A quantitative, descriptive, inferential, and cross-sectional study was undertaken to address this gap. Data were gathered from 410 employees of small and medium sized Brazilian family businesses operating in the state of Rio Grande do Sul. Participants answered a questionnaire consisting of two scales: (i) the Management Style Assessment Scale and (ii) the Supervisor-Subordinate Conflict Scale. In the family businesses in question, three managerial styles (situational, task, and relationship) were identified along with their contribution to conflicts. The ‘relationship’ style stood out as mitigating such events. These findings may provide insights regarding the theory of management styles and conflicts in family businesses and could offer practical management strategies for such contexts.